THE EFFECTIVENESS OF SAPPAN WOOD EXTRACT (Caesalpinia sappan L.) AS AN ALTERNATIVE MATERIAL FOR DENTAL PLAQUE IDENTIFICATION - Shofara Abilia, Andini; Lilies Anggarwati, Astuti; Martalina, Elliana; Sjarief , Ismail; Nydia, Hanan (Journal of Health and Dental Sciences, 2024)
The main factor of periodontal disease is dental plaque, which is attached to the surface of the teeth and consists of microorganisms originating from saliva and food debris. Dental plaque has a transparent colour, so a disclosing agent is needed to identify it. Sappan wood (Caesalpinia sappan L.) is a plant that contains brazilin and flavonoids that can be used for natural colouring. This study aims to determine the effectiveness of sappan wood extract (Caesalpinia sappan L.) as an alternative material for dental plaque identification. The experiment was conducted by measuring the plaque index of 20 people who did not clean their teeth for 12 hours for two periods. The first period of examination used a tablet disclosing agent, and the second period used 75% sappan wood extract. The research data were analyzed for normality with the Shapiro-Wilk dan Paired T-test. The result showed a significant difference in the mean plaque index score in the first period (1.3470) and the second period (1.0375) (p<0.05). It was concluded that staining dental plaque using a disclosing agent is more effective than 75% sappan wood extract (Caesalpinia sappan L.) DOI : 10.54052/jhds.v4n1.p47-56